Sur les jeux antagonistes joués en espaces fonctionnels - Janovskaja, J. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Е. Б. Яновская. Об антагонистических играх, разыгрываемых на функциональных пространствахJ. Janovskaja. Apie antagonistinius lošimus funkcionalinėse erdvėse